1995
DOI: 10.1021/bi00001a002
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specificity of the Second-Site Suppressor Mutation of the Asp-285 .fwdarw. Asn Mutant of Metal-Tetracycline/H+ Antiporter of Escherichia coli and the Effects of Amino Acid Substitutions at the First and Second Sites

Abstract: The deleterious effect of the mutation of Asp-285 to Asn of the metal-tetracycline/H+ antiporter (TetA) of Escherichia coli is suppressed by the second-site mutation of Ala-220 to an acidic amino acid residue (Yamaguchi, A., O'yauchi, R., Someya, Y., & Sawai, T. (1993) J. Biol. Chem. 268, 26990-26995). In this study, site-specific second-site Glu mutants as to 11 different positions around position 220 were established from the Asp-285-->Asn mutant TetA protein. Among them, only the Ala-220-->Glu mutant comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…For the mutagenesis, plasmid pCTC377A (12) was used as a template, where the Cys 377 3 Ala mutation was introduced into pCT1183 (19), which carries the 2.45-kilobase pair Tn10 tetA and tetR gene fragments. Mutations were detected as the appearance of a newly introduced restriction site and verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…For the mutagenesis, plasmid pCTC377A (12) was used as a template, where the Cys 377 3 Ala mutation was introduced into pCT1183 (19), which carries the 2.45-kilobase pair Tn10 tetA and tetR gene fragments. Mutations were detected as the appearance of a newly introduced restriction site and verified by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Each is also conserved in all members of the aromatic acid/H ϩ symporter family of the MFS. In TetA, a histidine residue and aspartate residues located in transmembrane domains have been identified as being required for the exchange of tetracycline and a H ϩ (25,29,30). Extensive studies on the lactose permease have identified pairs of charged amino acid residues (a negatively charged side chain paired with a positively charged side chain) in transmembrane helices that are involved in substrate translocation, H ϩ translocation, or helix packing (7,12,20).…”
Section: Mutant Pcak Proteins Did Not Have Defects In Membrane Localimentioning
confidence: 99%
“…Intragenic second-site suppression can either result from direct physical interactions among the amino acid residues affected by initial and suppressing mutations, or from global stabilization of a protein by the suppressing mutation. Intragenic second-site suppressors have previously been used to identify helix-helix interactions in several transmembrane proteins (Miller et al, 1990;King et al, 1991;Howitt & Cox, 1992;Lee et al, 1992;Sahin-Toth et al, 1992;Na et al, 1993;Someya et al, 1995). On the other hand, global second-site suppressors that are capable of suppressing a number of different initial loss-of function mutations have provided new information about the cooperativity and structural stability of proteins (Shortle & Lin, 1985;Das et al, 1989, Shortle, 1992Schiffer et al, 1995).…”
Section: Introductionmentioning
confidence: 99%